Methane potential from anaerobic co-digestion of sewage sludge and food waste in a stirred batch reactor - Sulaiman, Siti Mariam (2022)
Anaerobic digestion is a promising method for organic waste stabilization, including food waste and sewage sludge. Anaerobic digestion can be completed either in mono digestion or co-digestion, respectively; no longer limited to waste stabilisation method but also towards renewable energy production in the form of methane. The cosubstrate, a mixture of two or more organic waste, was used as a substrate in anaerobic co-digestion. The effect on co-digestion of municipal sewage sludge and food waste has been reported previously. However, there is less information on the digestibility of co-substrate, specifically a mixture of domestic sewage sludge and food waste. Hence, this study was conducted to examine the characteristics of the mixture of domestic sewage sludge and food waste, to compare the methane yield from a batch test of mesophilic anaerobic co-digestion and to determine the best fit between laboratory and modelling analysis of methane kinetics. Two sets of batch biochemical methane potential (BMP) test were conducted using Automatic Methane Potential Test System (AMPTS II); each for digestion of co-substrate; 1) a mixture of primary sewage sludge and food waste (PSS+FW) and 2) a mixture of secondary sewage sludge and food waste (SSS+FW). The results showed that the addition of food waste to domestic sewage sludge improved volatile solids to total solids (VS/TS) ratio. Between two co-substrates, PSS+FW showed better digestibility shown by 530.4mL methane accumulated, ultimate methane yield of 1233.57 mL CH4/g VS and methane production rate of 625.18 CH4/gVS day. Modified Gompertz modelling found fit well to the laboratory data indicatedby R2 of 0.997. In conclusion, co-digestion improved the synergy effect between organic substrates, indicated by improved volatile solid, VS to total solid, TS (VS/TS) ratio; and increased the efficiency of the anaerobic process shown by high methane production at early stage of the digestion inline with no lag phase.